RANCANG BANGUN ALAT PENGEMAS TERASI Design and construction of shrimp paste packaging - Muhammad Iqbal; Taufik Rizaldi; Achwil Putra Munir (Jurnal Rekayasa Pangan dan Pertanian, 2018)
ABSTRACT Packaging is a way of safeguarding the food to preserve the quality as well as its freshness. Manual package of shrimp paste was considered not attractive and slow as the shape of the paste was not the same and reduced the price of shrimp paste. The purpose of this research was to design, build, test and analyze the economic value of shrimp paste packaging. This research was conducted in September until november 2016 in the Laboratory of Agricultural Engineering, Faculty of Agriculture, University of North Sumatra, Medan, by literature study, equipment tests and parameters observation. The parameters observed were effective capacity and economic analysis.Based on this research, it was summarized that the effective capacity of the equipment was 144,25 package/hour. Economic analysis was Rp 95,55/package. Net present value (NPV) for interest rates of 16%  was Rp 53.251.518 and for interest rates of 20% was Rp 48.37.515. Internal rate of return (IRR) was 59,26%. Keywords: shrimp paste, molder, dynamo ABSTRAK   Pengemasan merupakan suatu cara pengamanan terhadap bahan pangan untuk mengawetkan mutu serta kesegarannya. Pengemasan terasi secara manual dinilai lambat dan kurang menarik karena bentuk yang tidak seragam dan mengurangi nilai jual terasi  Penelitian ini bertujuan untuk merancang, membuat, menguji serta menganalisis nilai ekonomis alat pengemas terasi. Penelitian ini dilakukan pada bulan Oktober hingga November 2016 di Laboratorium Keteknikan Pertanian, Fakultas Pertanian Universitas Sumatera Utara, Medan, dengan cara studi literatur, pengujian alat dan pengamatan parameter. Parameter yang diamati yaitu kapasitas efektif alat dan analisis ekonomi. Dari hasil penelitian diperoleh kapasitas efektif alat sebesar 144,25 buah/jam. Analisis ekonomi, biaya untuk mengemas terasi Rp 95,55/buah . Alat ini akan mencapai nilai break even point (BEP) apabila telah mengemas terasi sebanyak 19122,88 buah/tahun. Net present value (NPV) dengan suku bunga 16% adalah sebesar Rp 53.251.518 dan suku bunga 20% adalah Rp 48.327.515. Internal rate of return (IRR) adalah sebesar 59,26%. Kata kunci: terasi, alat pengemas, dynamo